Penerapan Sak-Emkm Sebagai Dasar Penyusunan Laporan Keuangan Emkm ( Studi Kasus Pada Kopi Semilyar Di Surabaya) - Hugo Ramadhani Ibrahim Fanani; Adiati Trihastuti (Inisiatif: Jurnal Ekonomi, Akuntansi dan Manajemen, 2023)
SAK – EMKM (Financial Accounting Standards – Micro, Small and Medium Entities) issued by IAI on January 1 2018 aims to make it easier for EMKM actors to prepare financial reports. This research was conducted with the aim of knowing the application of SAK-EMKM as a basis for preparing EMKM financial reports for Semilyar Coffee in Surabaya. This study uses a qualitative method with a case study approach. The data used in this study were obtained through interviews and direct or indirect observation. The results of this study indicate that EMKM Kopi Semilyar in preparing financial reports has not implemented SAK-EMKM (Standard Financial Accounting for Micro, Small and Medium Entities) and only compiled financial records simply by the owner. In interviews and observations conducted by researchers, it was found that EMKM Kopi Semilyar did not yet have HR (Human Resources) who knew about the preparation of financial reports based on SAK-EMKM.